Critical role of anteiso-C15:0 fatty acid in the growth of Listeria monocytogenes at low temperatures. - Annous, B A (1997)
Listeria monocytogenes is a food-borne pathogen capable of growth at refrigeration temperatures. Membrane lipid fatty acids are major determinants of a sufficiently fluid membrane state to allow growth at low temperatures. L. monocytogenes was characterized by a fatty acid profile dominated to an unusual extent (> 95%) by branched-chain fatty acids, with the major fatty acids being anteiso-C15:0, anteiso-C17:0, and iso-C15:0 in cultures grown in complex or defined media at 37 degrees C. Determination of the fatty acid composition of L. monocytogenes 10403S and SLCC 53 grown over the temperature range 45 to 5 degrees C revealed two modes of adaptation of fatty acid composition to lower growth temperatures: (i) shortening of fatty acid chain length and (ii) alteration of branching from iso to anteiso. Two transposon Tn917-induced cold-sensitive mutants incapable of growth at low temperatures had dramatically altered fatty acid compositions with low levels of i-C15:0, a-C15:0, and a-C17:0 and high levels of i-C14:0, C14:0, i-C16:0, and C16:0. The levels of a-C15:0 and a-C17:0 and the ability to grow at low temperatures were restored by supplementing media with 2-methylbutyric acid, presumably because it acted as a precursor of methylbutyryl coenzyme A, the primer for synthesis of anteiso odd-numbered fatty acids. When mid-exponential-phase 10403S cells grown at 37 degrees C were temperature down-shocked to 5 degrees C they were able, for the most part, to reinitiate growth before the membrane fatty acid composition had reset to a composition more typical for low-temperature growth. No obvious evidence was found for a role for fatty acid unsaturation in adaptation of L. monocytogenes to cold temperature. The switch to a fatty acid profile dominated by a-C15:0 at low temperatures and the association of cold sensitivity with deficiency of a-C15:0 focus attention on the critical role of this fatty acid in growth of L. monocytogenes in the cold, presumably through its physical properties and their effects, in maintaining a fluid, liquid-crystalline state of the membrane lipids.